Rheological characterisation and effect of abiotic factors on the antimicrobial efficacy of chitosan-based hidrogels containing alpha-hydroxy acids - Ribeiro, H. M.; Marto, Joana; Chiari, Bruna Galdorfini [UNESP]; Raposo, Sara; Silva, A N; Duarte, A; Corrêa, Marcos Antonio [UNESP]; Isaac, Vera Lucia Borges [UNESP] (My University, 2013)
The aim of this study was to investigate the rheological properties and antibacterial efficacy of chitosan/ alpha-hydroxy acids (lactic acid and glycolic acid) and cellulose polymers, both in hydrogels, in order to produce a formulation with improved activity against Propionibacterium acnes and Staphylococcus aureus, which can potentially be used in the treatment of acne. The rheological characterisation of the hydrogels was examined using continuous shear and viscoelastic creep. The antibacterial activities of formulations were performed by the well diffusion and broth microdilution. The hydrogels formulated with only chitosan showed pseudoplastic behavior while the chitosan hydrogels with cellulose polymers presented viscoelastic properties. The antibacterial activity was proportional to AHA and chitosan concentration. It was enhanced at low pH values and with high molecular weight chitosan and did not change with the incorporation of two cellulose polymers. The antibacterial mechanism of chitosan has currently been hypothesized as being related to surface interference. The results show that chitosan - based hydrogels containing AHA and cellulose polymers are viscoelastic,indicating good applicability onto the skin, and they present bacterial activity under various experimental conditions.
Keywords: Hydrogels; Chitosan; Alpha-hydroxy acids; Rheology; Antibacterial activity